The housing market in Ukraine - Diakov, Vladyslav (Jihočeská univerzita, 2020)
The purpose of this thesis was to take a deeper look into the Ukrainian housing market, understand its problems and find or synthesize possible solutions. My primary motivation for writing this paper is a period in my life when my father bought me an apartment in Kyiv and I, having no experience dealing with Ukrainian housing market bureaucracy and corruption, had to do all the paperwork to become a legal owner of the property. I failed multiple times before I succeeded and experienced a lot of issues, I researched in this paper first hand. Due to the reasons explained in the paper, obtaining primary data about the Ukrainian housing market is virtually Impossible, therefore the main sources for this thesis were theoretical works of scientists and researchers and secondary statistics. In the process of research, it was discovered that some problems undermining the development of the housing market in Ukraine are more trivial and easily solvable than it was hypothesized. However, some of the problems turned out to be deep-seated and systemic. This thesis definitely shows that even though the problems of the Housing market in Ukraine are serious and very damaging, there are possible solutions that can be effective in solving or at least mitigating those issues.
The housing market in Ukraine
Keywords: Housing; construction; urban environment; reform; corruption; transparency; market; affordability; Housing; construction; urban environment; reform; corruption; transparency; market; affordability